2013
DOI: 10.1128/aac.00425-13
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Identification of Mutations Responsible for Heterogeneous Vancomycin-Intermediate Staphylococcus aureus (hVISA)-to-VISA Conversion in Laboratory-Generated VISA Strains Derived from hVISA Clinical Strain Mu3

Abstract: bHeterogeneous vancomycin-intermediate Staphylococcus aureus (hVISA) spontaneously produces VISA cells within its cell population at a frequency of 10 ؊6 or greater. We established a total of 45 VISA mutant strains independently obtained from hVISA Mu3 and its related strains by one-step vancomycin selection. We then performed high-throughput whole-genome sequencing of the 45 strains and their parent strains to identify the genes involved in the hVISA-to-VISA phenotypic conversion. A comparative genome study s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
65
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 53 publications
3
65
0
Order By: Relevance
“…It has also been shown that mutations to other regulatory genes, including rpoD selected here, can lead to the VISA phenotype in the Mu3 lineage (35). The selection of the cell wall synthesis enzyme pbp4, here implicated in the VISA phenotype, has been confirmed in other studies (35,36) and is related to its role in peptidoglycan cross-linking.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…It has also been shown that mutations to other regulatory genes, including rpoD selected here, can lead to the VISA phenotype in the Mu3 lineage (35). The selection of the cell wall synthesis enzyme pbp4, here implicated in the VISA phenotype, has been confirmed in other studies (35,36) and is related to its role in peptidoglycan cross-linking.…”
Section: Discussionsupporting
confidence: 57%
“…For example, members of two-component regulatory systems selected here, graR, vraS, and walR, have been implicated in the VISA phenotype via their effects on cell wall composition and capsule expression (4,(32)(33)(34). It has also been shown that mutations to other regulatory genes, including rpoD selected here, can lead to the VISA phenotype in the Mu3 lineage (35). The selection of the cell wall synthesis enzyme pbp4, here implicated in the VISA phenotype, has been confirmed in other studies (35,36) and is related to its role in peptidoglycan cross-linking.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of such susceptible and resistant isolates can then be used to identify the altered genetic determinant in the VISA strain. This approach has identified a variable number and kinds of mutations in different VISA isolates (18,28,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40).…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently affected gene was cmk -encoding cytidylate kinase. Reduction of cytidylase kinase activity in cmk mutants encouraged the hVISA-to-VISA conversion by thickening the cell wall and reducing the cell growth rate [29].…”
Section: Discussionmentioning
confidence: 99%